International Joint Conference SOCO'17-CISIS'17-ICEUTE'17 León, Spain, September 6-8, 2017, Proceeding (Advances in Intelligent Systems and Computing,, 2018)
This volume of Advances in Intelligent and Soft Computing contains accepted papers presented at SOCO 2017, CISIS 2017 and ICEUTE 2017, all conferences held in the beautiful and historic city of León (Spain), in September 2017. Soft computing represents a collection or set of computational techniques in machine learning, computer science and some engineering disciplines, which investigate, simulate, and analyze very complex issues and phenomena. After a through peer-review process, the 12th SOCO 2017 International Program Committee selected 48 papers which are published in these conference proceedings, and represents an acceptance rate of 45%. In this relevant edition a special emphasis was put on the organization of special sessions. Two special session was organized related to relevant topics as: Artificial Intelligence and Machine Learning Applied to Health Sciences and Soft Computing Methods in Manufacturing and Management Systems. The aim of the 10th CISIS 2017 conference is to offer a meeting opportunity for academic and industry-related researchers belonging to the various, vast communities of Computational Intelligence, Information Security, and Data Mining. The need for intelligent, flexible behaviour by large, complex systems, especially in mission-critical domains, is intended to be the catalyst and the aggregation stimulus for the overall event. One special session was organized related to the relevant topic of Identification, Simulation and Prevention of Security and Privacy Threats in Modern Communication Networks. After a through peer-review process, the CISIS 2017 International Program Committee selected 18 papers which are published in these conference proceedings achieving an acceptance rate of 38%. In the case of 8th ICEUTE 2017, the International Program Committee selected 8 papers, which are published in these conference proceedings.